Effects of seasonal vitamin D3 supplementation on strength, power, and body composition in college swimmers - Rockwell, M. S.; Frisard, M. I.; Rankin, J. W.; Zabinsky, J. S.; Mcmillan, R. P.; You, W.; Davy, K. P.; Hulver, M. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The purpose of this study was to evaluate the impact of fall season vitamin D3 supplementation on strength/power, body composition, and anabolic hormones in swimmers with optimal vitamin D status at summer`s end. Male and female National Collegiate Athletic Association Division I swimmers (N = 19) with optimal 25-hydroxyvitamin D [25(OH)D] randomly received 5,000 IU of vitamin D3 (VITD) or placebo (PLA) daily for 12 weeks while participating in swimming and strength and conditioning training (August-November). Before and after the intervention, the participants underwent blood sampling for analysis of serum 25(OH)D, parathyroid hormone, total testosterone, free testosterone, sex hormone-binding globulin, and insulin-like growth factor 1, dual-energy X-ray absorptiometry, and strength/power testing (bench press, squat, dead lift, standing broad jump, vertical jump, and dips and pull-ups). Sex was used as a covariate for analyses. The 25(OH)D was decreased by 44% in PLA (p < .05) and increased by 8% in VITD over the 12 weeks. Fat-free mass increased in VITD (56.4-59.1 kg; p < .05), but not PLA (59.4-59.7 kg; p < .01). Significant Group × Time interaction effects were observed for dead lift (F = 21.577, p < .01) and vertical jump (F = 11.219, p < .01), but no other strength/power tests. Total testosterone decreased similarly in both groups, but free testosterone decreased and sex hormone-binding globulin increased only in PLA (p < .01). There were no group differences or changes in insulin-like growth factor 1 with the intervention. The findings suggest that vitamin D supplementation is an efficacious strategy to maintain 25(OH)D during the fall season training and to enhance some aspects of strength/power and fat-free mass in swimmers. Further research on the relationship between vitamin D and anabolic hormones is needed.